Postcolonial biblical interpretation: a futile exercise? (Journal for Studies in Humanities and Social Sciences, 2014)
After modernism, interpretive approaches moved away from focussing only on language for seeking the meaning of texts. In biblical interpretation, the same trend emerged. Focus shifted to the periphery and even the historical (diachronic) and current (synchronic) “outsides” or contexts of the language of texts in order to establish meaning in specific texts and textual genres. “Postcolonial” interpretation followed this trend in most African contexts and became more popular in the after-colonial eras of African interpretive communities who have been liberated socially and politically, and with that, also literarily. The postcolonial interpretive exercise currently gains ground, but also fights criticism from the pure literalists.